Penyuluhan Pola Makan Seimbang Pada Siswa SMP Negeri 05 Kendari - Endang Mariatika; Aisya Sulistiani; Diana Ramadhani; Adhel Meylani; Fauziah; Elsa Elfania; Fahira Nahnu Aulia; Cristianti Sanda Pare; Adelia Dwi Atsa; Fatimah Azzahrah; Agista Try Adistia (STIKES Columbia Asia Medan, 2026)
A balanced diet is a daily dietary pattern that contains nutrients in types and amounts appropriate to the body's needs. Knowledge of balanced nutrition and healthy eating habits is an important factor in preventing nutritional problems among adolescents. A lack of understanding regarding appropriate food choices can lead to unhealthy eating behaviors. Therefore, nutrition education is needed to improve students’ knowledge and awareness of the importance of implementing a balanced diet in daily life. This counseling activity aimed to increase students’ knowledge regarding balanced dietary patterns. The activity was conducted on June 4, 2025, at State Junior High School 5 Kendari and involved 30 seventh-grade students as respondents. The counseling methods included lectures using PowerPoint media, an ice-breaking session in the form of the WHO six-step handwashing simulation, question-and-answer sessions, and interactive quizzes. Evaluation was carried out using pre-tests and post-tests to measure students’ knowledge levels before and after the counseling activity. The results showed an increase in the mean knowledge score from 68.40 in the pre-test to 89.67 in the post-test. The paired t-test analysis showed a Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a significant difference between pre-test and post-test results. In addition, students gave positive responses to the counseling activity, stating that the material was interesting, easy to understand, and enjoyable. These findings indicate that balanced diet counseling was effective in improving students’ knowledge regarding the implementation of healthy eating habits in daily life.